Zeylu mir’ati’z-zaman. Cild II : min vekai’i seneti 658 ila seneti 670 hicriyye = Dhail Miratu’z-zaman or supplement to the mirror of the age. Vol. II : 658-670 A. H./1260-1271 A. D. - el-Yunini, Kutbüddin Ebi’l-Feth Musa b. Muhammed b. Ahmed b. Kutbüddin el-Balebekki el-Hanbeli, ?-1326 (Haydarabad)
[32], 489, 152, [6] s.